OSTEOTOMI LE FORT I DALAM BEDAH ORTHOGNATIK - Zulkarnain A. M. Zulkarnain; Abdul Latif; Pradono Pradono; Andri Anggraeni (Journal of Dentistry Indonesia, 2015)
Le Fort I osteotomy is the surgery in the maksila similar to the live fracture of the Fort I. In orthognathic surgery, Le Fort I osteotomy is the best choice for the conventional vertical dimension and relatively easy and middle and sufficient to reposition and maxilla. For the open bite case anteriory and postering in the patient could be performed. Le Fort I osteotomy in the posterior and the repositioned part of maxilla toward posuride so it could be occluded, functional and restored in the intended aesthetic.